Negative Emotions as Barriers to Translation Accuracy in Academic Settings - Al Ismail, Yazid Abdulrahman (Forum for Linguistic Studies, 2025)
This study investigates the effects of emotional negativity on translation performance, focusing on task duration, spelling accuracy, and comprehension of the source text. Emotional factors are increasingly recognized as influencing translators’ cognitive processes, particularly under time pressure or evaluative conditions. Forty-eight Arabic-speaking undergraduate translation students, representing both junior and senior levels, showed interest and agreed to participate voluntarily. Emotional negativity was measured using a self-report adaptation of Fredrickson’s Positivity Ratio framework, which captures the relative balance between positive and negative affect. Following this assessment, participants completed an Arabic-to-English translation task. The performance was evaluated for overall error score, spelling errors, and source-text (ST) misunderstandings to provide a comprehensive picture of translation quality. Results indicated that higher negativity was associated with longer completion times and more frequent ST misunderstandings. Group comparisons confirmed slower performance in the high-negativity group, whereas the difference in misunderstandings was directionally consistent but not statistically significant. No relationship emerged between negativity and either overall translation error score or spelling errors. These findings suggest that negativity primarily impairs processing efficiency and comprehension while leaving linguistic mechanics intact. Translator training programs may therefore benefit from incorporating emotional regulation strategies to help students sustain efficiency and accuracy under real-world professional demands.